"A hard day's night?" The effects of Compressed Working Week interventions on the health and work-life balance of shift workers: a systematic review. Issue 9 (13th August 2008) - Bambra, C; Whitehead, M; Sowden, A; Akers, J; Petticrew, M
Abstract : Objective: To systematically review studies of the effects of the Compressed Working Week on the health and work-life balance of shift workers, and to identify any differential impacts by socio-economic group. Methods: Systematic review. Following QUORUM guidelines, published or unpublished experimental and quasi-experimental studies were identified. Data were sourced from 27 electronic databases, websites, bibliographies, and expert contacts. Results: Fourty observational studies were found. The majority of studies only measured self-reported outcomes and the methodological quality of the included studies was not very high. Interventions did not always improve the health of shift workers, but in the five prospective studies with a control group, there were no detrimental effects on self-reported health. However, work-life balance was generally improved. No studies reported differential impacts by socio-economic group; however, most of the studies were conducted on homogeneous populations. Conclusion: This review suggests that the Compressed Working Week can improve work-life balance, and that it may do so with a low risk of adverse health or organisational effects. However, better designed studies that measure objective health outcomes are needed.